Enhancement of fructosyltransferase stability by immobilization on polyhydroxybutyrate and glutaraldehyde‐activated polyhydroxybutyrate for fructooligosaccharides production. Issue 2 (2nd November 2022) - Araújo, Isabella Medeiros; Becalette, Pedro Capalbo; da Silva, Elda Sabino; de Souza Dias, Giancarlo; da Cunha Abreu Xavier, Michelle; de Almeida, Alex Fernando; Maiorano, Alfredo Eduardo; Morales, Sergio Andres Villalba; Perna, Rafael Firmani
Abstract: BACKGROUND: Fructosyltransferase (FTase) enzyme is an important biocatalyst for fructooligossaccaride (FOS) production, but it has low stability in soluble form. The aim of this work was to analyze the stability and kinetics of an fructosyltransferase (FTase E.C.2.4.1.9) from Aspergillus oryzae IPT‐301 immobilized on polyhydroxybutyrate (PHB) and glutaraldehyde‐activated polyhydroxybutyrate (GLU‐PHB). RESULTS: The immobilization yields of the FTase on PHB and GLU‐PHB were about 41% and 55%, respectively. The recovery activities of the FTase immobilized on PHB and GLU‐PHB were about 17% and 11%, respectively. At 30 °C, the FTase immobilized on GLU‐PHB showed a half‐life 2.6 and 1.4 times higher than the soluble FTase and the FTase immobilized on PHB, respectively. The FTase immobilized on PHB and GLU‐PHB retained more than 40% and 55% of their initial activity after six sequential reaction batches, respectively. Both immobilized enzymes showed kinetic behaviors that were fitted by the Hill model, with transfructosylation activity maximum at concentrations between 400 g substrate L −1 and 500 g substrate L −1 . CONCLUSION: These results demonstrate that the FTase immobilized on PHB and, especially, on GLU‐PHB, are promising biocatalysts for FOS production in heterogeneous reaction systems. © 2022 Society of Chemical Industry (SCI).